Ethical and cognitive challanges in the COVID-19 emergency - Chiara Lucifora; Gustavo Cevolani (Rivista Internazionale di Filosofia e Psicologia, 2020)
The global emergency caused by the spread of COVID-19 raises critical challenges for individuals and communities on many different levels. In particular, politicians, scientists, physicians, and other professionals may face new ethical dilemmas and cognitive constraints as they make critical decisions in extraordinary circumstances. Philosophers and cognitive scientists have long analyzed and discussed such issues. An example is the debate on moral decision making in imaginary scenarios, such as the famous “Trolley Problem”. Similarly, dramatic and consequential decisions are realized daily in the current crisis. Focusing on Italy, we discuss the clinical ethical guidelines proposed by the Italian Society of Anesthesiology, Analgesia, Resuscitation and Intensive Care (SIAARTI), highlighting some crucial ethical and cognitive concerns surrounding emergency decision making in the current situation.